Carbene footprinting reveals binding interfaces of a multimeric membrane spanning protein - Manzi, Lucio; Barrow, Andrew; Hopper, Jonathan; Kaminska, Renata; Kleanthous, Colin; Robinson, Carol; Moses, John; Oldham, Neil (Wiley-VCH Verlag, 2017)
Mapping the interaction sites between membrane spanning proteins is a key challenge in structural biology. In this study a carbene footprinting approach is developed and applied to identify the interfacial sites of a trimeric, integral membrane protein, OmpF, solubilised in micelles. The diazirine-based footprinting probe is effectively sequestered by, and incorporated into, the micelles leading to efficient labelling of the membrane-spanning regions of the protein upon irradiation at 349 nm. Areas associated with protein-protein interactions between the trimer subunits remained unlabelled, thus revealing their location.